2012
DOI: 10.1111/j.1365-2044.2012.07227.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the European Working Time Directive on anaesthetic working patterns and training

Abstract: SummaryThere is concern that the European Working Time Directive 2009 has led to reduced time available for training, and this study examined if this has been the case. For two identical six-month periods in 1999 (pre-Directive) and 2009 (postDirective), weekly data were collected on the total number of sessions attended by trainees, the number of supervised sessions and the leave days taken. A total of 5925 theatre sessions were analysed (2353 in 1999 and 3572 in 2009). For ST1-2 trainees, there was a 37% inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 7 publications
0
14
0
Order By: Relevance
“…Traditionally, rotas are written to plan activity for the week ahead, but changes occur throughout the week and are not always captured by monitoring systems. The electronic rota system, CLWRota (Rotamap Ltd, London, UK; see http://clwrota.com) , has become widely used throughout the UK. It provides an accurate, electronic record of actual staffing of sessions, rather than the planned allocation, as changes are tracked in real time throughout the life‐cycle of a week's rota.…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, rotas are written to plan activity for the week ahead, but changes occur throughout the week and are not always captured by monitoring systems. The electronic rota system, CLWRota (Rotamap Ltd, London, UK; see http://clwrota.com) , has become widely used throughout the UK. It provides an accurate, electronic record of actual staffing of sessions, rather than the planned allocation, as changes are tracked in real time throughout the life‐cycle of a week's rota.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well documented that the EWTR has reduced the individual's time for training . However, a more recent issue has surfaced, namely workforce difficulties.…”
Section: Why Is Experience Lower Within a Training Programme Than Befmentioning
confidence: 99%
“…The anaesthesia literature contains no evidence of any reduction in anaesthetic trainees' caseload or access to training opportunities and shows consistent exam success rates, no increase in referrals to regulatory bodies, 5 6 and a reduction in sick leave among trainees since the regulations were introduced. 7 Data from the Royal College of Anaesthetists show that most trainees continue to complete workplace based assessments on time. 8 The Royal College of Paediatrics and Child Health reported that reconfiguration of acute services and implementation of consultant delivered care in response to the working time regulations had maintained adequate exposure to training opportunities.…”
Section: Catalyst For Redesignmentioning
confidence: 99%